2019
DOI: 10.11646/zootaxa.4563.3.8
|View full text |Cite
|
Sign up to set email alerts
|

A molecular phylogeny of the genus Psittacula sensu lato (Aves: Psittaciformes: Psittacidae: Psittacula, Psittinus, Tanygnathus, †Mascarinus) with taxonomic implications 

Abstract: The long-tailed parakeets of the genus Psittacula Cuvier, 1800 have thus far been regarded as a homogeneous and monophyletic group of parrots. We used nucleotide sequences of two genetic markers (mitochondrial CYTB, nuclear RAG-1) to reconstruct the phylogenetic relationships of Psittacula and closely related species. We found that the Asian genus Psittacula is apparently paraphyletic because two genera of short-tailed parrots, Psittinus Blyth, 1842 and Tanygnathus Wagler, 1832, cluster within Psittacula, as d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…and genetic proximity to Psittacula roseata [8,14]. A number of studies on evolutionary, morphological, and systematic aspects of the Psittacula genus have highlighted taxonomic ambiguities such as the paraphyletic nature of certain species and cladding of the genus Tanygnathus within the genus Psittacula [8,14,15,16].…”
Section: P Cyanocephala Bears Close Morphological Resemblance In Termentioning
confidence: 99%
See 3 more Smart Citations
“…and genetic proximity to Psittacula roseata [8,14]. A number of studies on evolutionary, morphological, and systematic aspects of the Psittacula genus have highlighted taxonomic ambiguities such as the paraphyletic nature of certain species and cladding of the genus Tanygnathus within the genus Psittacula [8,14,15,16].…”
Section: P Cyanocephala Bears Close Morphological Resemblance In Termentioning
confidence: 99%
“…A number of studies on evolutionary, morphological, and systematic aspects of the Psittacula genus have highlighted taxonomic ambiguities such as the paraphyletic nature of certain species and cladding of the genus Tanygnathus within the genus Psittacula [8,14,15,16]. Recently, Braun and coworkers reconstructed the phylogenetic tree of Psittacula and other closely related species using differences in nucleotide sequences of two genetic markers (mitochondrial cob and nuclear rag1 gene) and observed that the Asian genus Psittacula is paraphyletic [8]. To create monophyletic genera, Braun and coworkers proposed the recognition of genus Himalayapsitta Braun, 2016 for P. himalayana, P. finschii, P. roseata, and P. cyanocephala [8].…”
Section: P Cyanocephala Bears Close Morphological Resemblance In Termentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular studies supported closely related with P. roseata and P. cyanocephala by highly probability based on cytochrome-b gene (Kundu et al 2012). Psittacula roseata was the basal lineage within Himalayapsitta cluster, P. cyanocephala-finschii were a sister clade to P. roseate based on cytochrome-b gene, RAG-1 (Braun et al 2019). The complete mitochondrial genome of P. roseata has not been determined and characterized until now.…”
mentioning
confidence: 99%